Egg Quality of Layer Hens Reared in Two Different Housing Systems - Salnan Irba Novaela Samur; Risma Novela Esti (Universitas Veteran Bangun Nusantara, 2024)
This study aims to determine whether there is a significant difference in the quality of eggs from chickens raised in closed-house and open-house cages. This study was conducted in Close housed and house cages for Isa Brown strain layer chickens in the Blitar Regency area in May 2024. The materials used in this study were 40 eggs of 68-week-old Isa Brown strain chickens kept in closed houses and open houses. This research was conducted using an experimental quantitative method using an unpaired t-test, which was analyzed using the Microsoft Excel application. The results showed that the egg weights of chickens reared in the closed house and open house were 63.80 g and 59.68 g; the egg index was 79.06 from the closed house cage and 76.19 from the open house cage. The Yolk index was 0.65 from the closed-house cage and 0.74 from the open-house cage. Haugh Unit (HU) 61.90 from the closed house cage and 64.40 from the open house cage. This study concludes that there is a significant difference in the quality of eggs from chickens reared in closed and open houses. The best egg weight and index were found in chickens reared in a closed house. At the same time, the best yolk index and HU were found in eggs from hens reared in open houses.